Tinjauan Teologis terhadap Musik Gereja Kontemporer - Luluhati Telaumbanua; Toni Salurante (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The development of contemporary church music, as part of the dynamic life of Christian worship, has sparked various responses—both as a relevant cultural expression and as a potential theological deviation. Music that adopts popular styles and emotionally expressive forms is often considered effective in engaging younger generations, yet it also raises concerns about shifting the focus of worship from God to human experience. This article aims to theologically examine the presence of contemporary church music in light of biblical principles of Christian worship. The method used is a descriptive qualitative literature study, drawing from theological works and research published within the last five years. The findings show that although contemporary music can serve as an effective means of fostering congregational spirituality, it must be theologically tested to ensure that musical expression does not obscure the Christ-centered essence of worship. Therefore, the church is called to integrate contemporary music into liturgy with discernment and theological responsibility.